Odpowiedzi

Najlepsza Odpowiedź!
  • Użytkownik Zadane
2010-04-15T16:53:27+02:00
A) 3\x-2 = 4\2x+1
3(2x+1)=4(x-2)
6x+3=4x-8
2x=-8-3
2x=-11
x=-5,5

b) 2\3 = 3x+2\2x-2
2(2x-2)=3(3x+2)
4x-4=9x+6
4x-9x=6+4
-5x=10
x=-2

c) 6x-1\x+1 = 2,3\1,2
1,2(6x-1)=2,3(x+1)
7,2x-1,2=2,3x+2,3
7,2x-2,3x=2,3+1,2
4,9x=3,5
x=35/49
x=5/7

d) -x\3x-1 = 2x\1-6x
-x(1-6x)=2x(3x-1)
-x+6x^2=6x^2-2x
-x+2x=0
x=0
14 4 14
2010-04-15T16:54:52+02:00
A) 3\x-2 = 4\2x+1
3x-2=2x+1 / +2
3x=2x+3 /-2x
x=3
b) 2\3 = 3x+2\2x-2 /*6
6*⅔=18x+ 6 * 2/2x - 12
4=18x+6x-12 /+12
16=24x / :24
x=16/24
x=⅓
c) 6x-1\x+1 = 2,3\1,2 / * 1,2
7,2x-1,2x+1,2=2,3 /-1,2
6x=1,1 /:6
x= 1,1/6 -- ułamek
d) -x\3x-1 = 2x\1-6x
-3x-1=2x-6x/+3x
-1=-x / : (-1)
x=1

licze na naj !
10 2 10